Nursing care for women with pre-eclampsia and/or eclampsia: integrative review - Maria Beatriz Guimarães Ferreira; Caroline Freitas Silveira; Sueli Riul da Silva; Delvane José de Souza; Mariana Torreglosa Ruiz (SciELO, 2016)
Abstract OBJECTIVE: To analyze the available evidence in the literature on nursing care for women with pre-eclampsia and/or eclampsia. METHODS: Integrative review searching for primary studies in the databases PubMed, CINAHL, LILACS and SciELO. RESULTS: The sample size consisted of 17 primary studies published between January 2000 and December 2014, grouped into four categories: standardizing blood pressure measurement technique; training with simulation; instruments for standardization of care and quality of care The main nursing actions were: physical examination, early detection of signs of pre-eclampsia/eclampsia, monitoring of laboratory tests, fetal assessment, qualification and training of professionals. We identified the need for standardization of care from instruments, protocols and blood pressure measurement technique, early identification and treatment of hypertensive crisis through institutional protocols and review of cases and work processes. CONCLUSION: Women with pre-eclampsia and/or eclampsia require specific nursing care, which must be guided by care protocols based on scientific evidence.